The Distribution of Relative Clauses in Chinese Discourse - Pu, Ming-Ming (Discourse processes, 2007)
The particular forms of relative clauses (RCs) in Mandarin Chinese lead to particular cognitive, semantic, pragmatic, and discourse constraints on speakers and writers. In this study, analyses of oral and written Mandarin Chinese narratives demonstrate that SS structures (subject head noun phrase [NP] modified by a subject RC) are produced more frequently than OS (object head NP modified by subject RC) and OO structures (object head NP modified by object RC), which are more frequent than the rare SO (subject head NP modified by an object RC) structure. These patterns can be explained by the interaction of cognitive strategies of closure and the semantic and discourse functions of RC constructions. In particular, the center-embeddedness of Mandarin Chinese RCs likely leads to greater cognitive load for speakers than writers, and the fact that head NPs are more likely to refer to humans helps predict the predominance of the SS pattern.